Brachemys (Atelestodes) minotaurus sp.n., a new coastal Malachiidae (Coleoptera) from Crete - Hernando, Carles; Ribera, Ignacio (Zootaxa, 2019)
A new species of the costal genus Brachemys Abeille de Perrin, 1890 is described from Crete, B. minotaurus n.sp. (Coleoptera, Malachiidae). The species is included in the subgenus Atelestodes Abeille de Perrin, 1890 due to the lack of modified protarsi, although the subgeneric classification of Brachemys may need to be revised. Specimens of the new species were found running on bare rock in the supralittoral zone, bearing a striking resemblance to ants.